Frequency of Partial Edentulism among a Sample of Patients Presenting to a Tertiary Care Hospital - Zahid Naeem, Rozeena Farooq, Muhammad Usman Ashraf, Arooba Mehmood, Afnan Rahman, Farhan Raees, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The oral cavity's primary structural and functional elements are teeth. In addition to mastication, speaking, and aesthetics, teeth also serve other purposes. Lack of teeth in the oral cavity causes problems with communication, bad aesthetics, and trouble chewing food, all of which have a significant impact on quality of life. Objective: To find out the frequency of partial edentulism. Study Design: Descriptive cross sectional study Place and Duration of Study: Department of Prosthodontics, Bacha Khan College of Dentistry, Mardan from November 2022 to April 2023. Methodology: Two hundred and ninety three patients of both genders aged 16-60 years and residents of Mardan assessed on basis of NIC were included while completely edentulous patients i.e. patients who have lost all of their teeth, handicapped patients, patients with limited mouth opening, patients currently undergoing orthodontic treatment and patients with a maxillary obturator for a cleft palate were excluded. Results: The mean age of study was 39.70±14.876 with range from 18 to 75 years. There were 239 (81.6%) missing teeth to some extents i.e. partially dentate and 54 (18.4%) did not exhibit any missing teeth, completely dentate while 151 (51.5%) males and 142 (48.5%) females. Conclusion: The prevalence of partial edentulism was to be 81.6%. Correlation of partial edentulism with gender demonstrated that prevalence of partial edentulism was slightly higher in females. Keywords: Partial edentulism, Prosthodontics, Age, Gender, Occupation, Education Level, Socioeconomic status, Number of missing teeth, Oral hygiene status